O comportamento alimentar em crianças : estudo de validação de um questionário numa amostra portuguesa (CEBQ) - Viana, Victor (2008)
The aim of this research was to validate de Child EatingBehaviour Questionnaire (CEBQ) in a Portuguese sample.Participants were 249 subjects aged 3 to 13 years, fromboth gender. Factor analysis, Homogeneity analysis and Internal reliability, as the theory beyond proposed,confirmed a structure with eight factors that were: Enjoyment of food, Food responsiveness, Satiety responsiveness, Slowness in eating, Fussiness, Emotional overeating, Emotional undereating and Desire to drink. The distribution of the results of the eight sub scales by groupsof subjects organized by BMI types, classified as underweight, normal weight, over weight and obese, shows that the questionnaire can successfully discriminate thosegroups. In spite of the lack of representativeness of thesample selected for this study, conclusions are that CEBQseems to be adequate to the research of eating behaviourand eating style in the Portuguese young population, and can be used to design behavioural interventions in obese children.